2007
DOI: 10.1124/dmd.106.014449
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition of a Selective α7 Nicotinic Acetylcholine Receptor Agonist in Humans

Abstract: ABSTRACT:The The formation of 2 was found to be mediated by CYP2D6, a polymorphically expressed enzyme absent in 5 to 10% of white people, whereas the generation of 4 was catalyzed by CYP2D6, FADcontaining monooxygenase 1 (FMO1), and FMO3. It is of interest that, although no overall gender-related differences in excretory routes, mass recoveries, pharmacokinetics, or metabolite profiles of 1 were evident, the observation of one of eight subjects (13%) showing disparate (relative to all other volunteers) system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
4
19
0
1
Order By: Relevance
“…However, there are a few prior examples of CYP2D6-mediated formation of N-oxide. Procainamide (Lessard et al, 1999), sparteine , citalopram (Olesen et al, 1999) (Shaffer et al, 2007) probably are the only limited number of compounds reported previously to have N-oxidation catalyzed by CYP2D6.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a few prior examples of CYP2D6-mediated formation of N-oxide. Procainamide (Lessard et al, 1999), sparteine , citalopram (Olesen et al, 1999) (Shaffer et al, 2007) probably are the only limited number of compounds reported previously to have N-oxidation catalyzed by CYP2D6.…”
Section: Discussionmentioning
confidence: 99%
“…PHA-543613 and PHA-568487 exhibited sufficient preclinical efficacy and safety to support their advancement into phase I single-ascendingdose and multiple-ascending-dose safety, tolerability and pharmacokinetic studies. PHA-543613 also demonstrated a linear pharmacokinetic profile and a desirable half-life in human subjects (approximately 9-12 h) [79]. CogState battery testing of PHA-543613 and PHA-568487 revealed a modest improvement in cognitive function at low doses of 6 mg twice a day; however, a low frequency of cardiovascular arrhythmia with no evidence of QTc prolongation or other electrocardiographic interval changes was also observed in these studies.…”
Section: A 7 Receptor Agonists In Clinical Trials For Schizophreniamentioning
confidence: 91%
“…6,22,32,42 Furthermore, although the optimal timing of drug administration is not currently known, the preclinical data support postictus drug administration. In particular, in the study described above, Hijioka et al administered PNU-282987 at different initial time points relative to ICH onset (1 hour prior, and 3, 6, and 12 hours after), and demonstrated a time-dependent decline in efficacy that remained statistically significant until 6 hours after ICH onset, with the greatest efficacy being observed with initial dosing at 3 hours after ICH onset.…”
Section: Clinical Feasibility Of An α7-nachr Agonist As a Novel Theramentioning
confidence: 98%